Jordan Economic Monitor, June 2020 : Weathering the Storm - World Bank (World Bank, Washington, DC, 2020)
The COVID-19 pandemic has created a severe global recession. The global economy, after showing a moderate recovery in 2019, is currently reeling from the Coronavirus (COVID-19) pandemic which, besides taking a toll on human life, has pushed the global economy into the worst recession since the Great Depression due to the lockdowns aimed at controlling the spread of the virus. Starting as a supply shock, the pandemic has triggered an unprecedented demand shock that led to significant decline in global commodity prices, especially oil prices. The lockdowns have also amplified pre-existing vulnerabilities such as weak governance, large labor market informality, and limited fiscal space. This constrained fiscal space, for example, limits countries'room to maneuver with already high levels of debt and tightening external financing conditions. The recent global developments along with domestic disruptions due to pandemic measures are severely impacting the already struggling Jordanian economy and its prospects. For the fourth year in a row, in 2019 Jordan's economy continued to drift around a tepid 2.0 percent growth rate. Such a growth rate is not sufficient to tackle some pressing socio-economic issues, such as a low labor force participation and high unemployment, particularly among women and youth. On the macro front, while there was significant reduction recorded in external imbalances during 2019, supported by healthy growth in exports and travel receipts, fiscal policy remained expansionary and pushed the debt-to-GDP ratio to almost 100 percent. Within this context, the country is facing significant economic challenges due to the COVID-19 pandemic through both external and domestic channels. These challenges are amplified because Jordan has large linkages to the external world.